Physical map of the conjugal plasmid of Neisseria gonorrhoeae. - Tenover, F C (1980)
The 24.5-megadalton plasmid of Neisseria gonorrhoeae is required for transfer of R-factors and possibly chromosomal markers during conjugal matings between gonococcal strains. We constructed a physical map of one such plasmid, pLE2451, using EcoRI, BglII, and HincII site-specific restriction endonucleases. The patterns of deoxyribonucleic acid digestion obtained with this plasmid were identical to those obtained with three other plasmids of similar size.